Analisis Perbandingan Produktivitas Jam Kerja pada Proyek Reparasi Kapal TB. Ampenan 01 dengan Metode Critical Path Method & Critical Chain Project Management di Galangan Kapal Madura - Rizky Saputra Aminata; Minto Basuki (Fakultas Teknik Universitas Maritim AMNI Semarang, 2023)
This final assignment compared the results of durations in the CCPM method and the Critical Path Method (CPM) by conducting a case study of ship repairs at Galangan Kapal Madura Ltd. Initial project scheduling employed the traditional method of a Gantt chart, which was then broken down in more detail and complete relationships among activities into CPM form. The results were then compared with the duration in CCPM scheduling by eliminating multitasking and safety time for each activity as well as providing a buffer in progress. The CPM method lasted for 30 days at a cost of IDR 246,600,000.00, while the CCPM method lasted for 20 days at a cost of IDR 215,600,000.00. In conclusion, the CCPM method was the most effective.